Effects of group acceptance and commitment therapy on psychological distress of patients with cervical cancer receiving chemotherapy and radiotherapy (团体接纳与承诺疗法对宫颈癌放化疗患者心理痛苦程度的影响) - LI Xia (李霞); LEI Yan (雷艳) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the effect of group acceptance and commitment therapy on psychological distress and quality of life in patients with cervical cancer receiving chemotherapy and radiotherapy. Methods Eighty-two patients with cervical cancer receiving chemotherapy and radiotherapy were randomly divided into control group and observation group. The control group received routine nursing, and the observation group was given group acceptance and commitment therapy based on the routine care. The scores of the Acceptance and Action Questionnaire-Second Edition(AAQ-Ⅱ), Distress Thermometer(DT) and Quality of Life Instruments for Cancer Patients-Cervix Cancer (QLICP-CE) were compared between two groups before and after the intervention. Results After intervention, AAQ-Ⅱ and DT scores of the observation group were lower than those of the control group, and QLICP-CE score was higher than that of the control group, with statistical significance (P＜0. 01)．Conclusion Group acceptance and commitment therapy is an effective psychological behavioral intervention to enhance psychological flexibility, relieve distress, and improve the quality of live for cervical cancer receiving chemotherapy and radiotherapy. (目的 探讨团体接纳与承诺疗法对宫颈癌同步放化疗患者心理痛苦和生活质量的影响。方法 将82例行同步放化疗的宫颈癌患者随机分为观察组和对照组, 各41例。对照组患者接受常规护理, 观察组在对照组基础上运用团体接纳与承诺疗法进行护理干预, 并于干预前后采用中文版接纳与行动问卷(AAQ-Ⅱ)、心理痛苦温度计(DT)、癌症患者生命质量测定量表之宫颈癌量表(QLICP-CE)进行评价。结果 干预后观察组AAQ-Ⅱ及DT得分低于对照组, QLICP-CE总分高于对照组, 差异有统计学意义(P<0. 01)。结论 团体接纳与承诺疗法可以显著降低宫颈癌同步放化疗患者的经验性回避水平, 提高心理灵活性, 减轻心理痛苦程度, 提高生存质量, 是一种有效的心理行为干预方法。)